2018
DOI: 10.1007/s00442-018-4298-9
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic effects of temperature and dissolved organic carbon on fish growth in California mountain lakes

Abstract: Resources and temperature play major roles in determining biological production in lake ecosystems. Lakes have been warming and 'browning' over recent decades due to climate change and increased loading of terrestrial organic matter. Conflicting hypotheses and evidence have been presented about whether these changes will increase or decrease fish growth within lakes. Most studies have been conducted in low-elevation lakes where terrestrially derived carbon tends to dominate over carbon produced within lakes. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 68 publications
(93 reference statements)
3
4
0
Order By: Relevance
“…During recent decades, lakes and many coastal waters across the northern hemisphere have become both warmer and browner (Creed et al, 2018). Similar to comparative lake studies (shown for trout in Symons et al, 2019 and for juvenile but not adult perch in van Dorst et al, 2019), we found that such higher temperatures and darker waters may have antagonistic effects on fish body growth. This suggest that the widespread notion of a temperature‐size‐rule, predicted to result in increased growth rates of juvenile fish (Atkinson, 1994), may not be general but context dependent—as positive physiological effects of warming can be negated by lower foraging efficiency in brown environments.…”
Section: Discussionsupporting
confidence: 90%
“…During recent decades, lakes and many coastal waters across the northern hemisphere have become both warmer and browner (Creed et al, 2018). Similar to comparative lake studies (shown for trout in Symons et al, 2019 and for juvenile but not adult perch in van Dorst et al, 2019), we found that such higher temperatures and darker waters may have antagonistic effects on fish body growth. This suggest that the widespread notion of a temperature‐size‐rule, predicted to result in increased growth rates of juvenile fish (Atkinson, 1994), may not be general but context dependent—as positive physiological effects of warming can be negated by lower foraging efficiency in brown environments.…”
Section: Discussionsupporting
confidence: 90%
“…There are few studies testing the impact of climate warming on somatic growth in salmonids; however, a study on rainbow trout revealed that a 2°C increase in water temperature enhanced growth throughout most of the growing season (Morgan, McDonald, & Wood, ). This is further supported by a recent study showing that freshwater salmonid populations experiencing climate warming within their temperature tolerance range will exhibit increased growth rates (Symons, Schulhof, Cavalheri, & Shurin, ). It is therefore likely that Arctic charr inhabiting areas where current water temperatures are substantially lower than the optimum for somatic growth will experience increased somatic growth and production from climate warming (Karlsson, Jonsson, & Jansson, ).…”
Section: Discussionsupporting
confidence: 54%
“…Climate change in combination with browning and eutrophication will alter the function and fuelling of aquatic food webs 158 . Indirectly, climate warming also affects lake ecosystems through changes in the landscape that lead to shifts in vegetation 159 or increased dust 160 that can affect nutrient availability, water quality, and community composition and productivity 161 .…”
Section: Implications For Lake Ecosystemsmentioning
confidence: 99%